2012
DOI: 10.1051/0004-6361/201218937
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal processes in bowshocks of runaway stars

Abstract: Context. Runaway massive stars are O-and B-type stars with high spatial velocities with respect to the interstellar medium. These stars can produce bowshocks in the surrounding gas. Bowshocks develop as arc-shaped structures, with bows pointing to the same direction as the stellar velocity, while the star moves supersonically through the interstellar gas. The piled-up shocked matter emits thermal radiation and a population of locally accelerated relativistic particles is expected to produce non-thermal emissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 54 publications
3
63
0
8
Order By: Relevance
“…As a result, this study does not concern massive X-ray and/or γ-ray binaries or microquasars that include a compact object (Fender & Maccarone 2004;Khangulyan & Aharonian 2005;Bosch-Ramon 2007;Bosch-Ramon & Rieger 2011) and is neither related to supernova remnants, known to be efficient particle accelerators (Romero 2004;Reynolds 2011;Vink 2013). Moreover, the class of objects debated does not include rapidlymoving runaway massive stars whose stellar wind interacts with the interstellar medium, producing strong shocks likely to accelerate particles (Benaglia et al 2010b;Romero et al 2011;Peri et al 2011;del Valle & Romero 2012).…”
Section: The Cataloguementioning
confidence: 99%
“…As a result, this study does not concern massive X-ray and/or γ-ray binaries or microquasars that include a compact object (Fender & Maccarone 2004;Khangulyan & Aharonian 2005;Bosch-Ramon 2007;Bosch-Ramon & Rieger 2011) and is neither related to supernova remnants, known to be efficient particle accelerators (Romero 2004;Reynolds 2011;Vink 2013). Moreover, the class of objects debated does not include rapidlymoving runaway massive stars whose stellar wind interacts with the interstellar medium, producing strong shocks likely to accelerate particles (Benaglia et al 2010b;Romero et al 2011;Peri et al 2011;del Valle & Romero 2012).…”
Section: The Cataloguementioning
confidence: 99%
“…Benaglia et al (2010) detected radio emission from the bow shock produced by the runaway star BD+43 3654, consistent with synchrotron radiation produced by the interaction of the relativistic electrons with the magnetic field of the acceleration region. Later, del Valle & Romero (2012) presented a nonthermal emission model that predicted the production of high-energy photons in these acceleration regions in sufficiently large numbers to be detected in X-rays. López-Santiago et al (2012) published the first detection of X-ray emission from a bow shock produced by a runaway star (AE Aurigae), while Terada et al (2012) reported the non-detection of X-ray emission in the bow shock region formed by BD+43 3654 from a long-duration X-ray observation with Suzaku.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we applied the model derived by del Valle & Romero (2012), where different nonthermal processes are proposed to explain the origin of the emission in these shocks. Further details on the nonthermal processes are also found in Adams (1980), Kelner et al (2006), Longair (2011) or Rybicki & Lightman (1979).…”
Section: Introductionmentioning
confidence: 99%
“…Instruments such as the Fermi Gamma Ray Space Telescope 1 , or the ground-based atmospheric imaging Cherenkov telescopes MAGIC 2 , H.E.S.S. 3 , and VERITAS 4 , among others, have been key to unveil new kinds of energetic sources. Outstanding among them there are the so called 'gamma-ray binaries' (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, other stellar gammaray sources have been predicted to exist based on theoretical work, although their firm detection remains yet to be accomplished. These include T-Tauri stars [2], bipolar outflows from massive protostars [3] as well as bowshocks from runaway stars [4].…”
Section: Introductionmentioning
confidence: 99%